A Fuzzy Self-tuning Controlled Feeding Servo System of Machine Tool - Yueshan Wang; Liwan Chen; Zenghan Chen (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The permanent magnet synchronous motor(PMSM) has been used widely for computer numerically controlled (CNC) feeding servo system (FSS) of machine tools. The control performance of the actual CNC-FSS depends on many parameters, and it has the properties of nonlinear uncertainty and time-varying characteristics. It is difficult to establish an accurate model for the actual CNC-FSS, therefore, a fuzzy self-tuning controller (FSC) of CNC-FSS was developed to overcome this problem in this paper. The proposed control strategy was based on fuzzy control theory combined with the conventional proportion integration differentiation (PID) control and its control algorithm. In this paper, we presented design of controller using FSC method and analyzed time response of the intelligent controller. Step response was plotted and analyzed to verify the effectiveness of the proposed controllers. Simulation results show that the FSC has minimum overshoot, minimum transient and steady state parameters, which shows the more effectiveness and efficiency of FSC than conventional PID controller to control the position of the CNC-FSS. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2459